THE STRUCTURE OF THE NON-PSYCHOTIC MENTAL (PSYCHIATRIC) DISORDERS IN PATIENTS WITH EPILEPSY WITH DIFFERENT VARIANTS OF THE DISEASE - N. A. Sivakova; A. P. Kotsubinskyi; L. V. Lipatova (Эпилепсия и пароксизмальные состояния)
Mental disorders persistent identified in patients with epilepsy as significant personal and affective disorders, especially depressive and anxiety spectrum observed in the interictal period of the disease.Purpose. Study the frequency of nonpsychotic mental disorders in patients with epilepsy; highlight the clinical features of non-psychotic affective disorders and to analyze the relationship of different variants affective disorders with symptoms of pharmacological resistance.Material and methods. The study involved 160 patients with epilepsy: 80 patients with drug-resistant epilepsy (DRE), 80 patients with controlled epilepsy using a battery of psychometric scales.Results. The variety of depressive and anxious psychiatric condition detected in 59.4% of patients with epilepsy, in 86.3% of patients with DRE, in 32.5% – with controlled epilepsy. Clinical and psychopathological analysis of non-psychotic mental disorders showed that in patients with DRE have statistically more frequent affective disorders, also a great “brutality”, “structural complexity” and the depth of depressive and anxiety disorders than in patients controlled epilepsy. We established that patients with affective symptoms have earlier onset and a longer course of disease.Conclusion. The therapeutic resistance of patients with epilepsy accompanied by the presence of various non-psychotic affective mental disorders represented, mainly, depressive and anxiety psychopathological conditions. In terms of clinical and psychopathological a characteristics they are close to an endogenous affective mental disorders and, essentially, represent their “organic model.”